Hydraulic Switching Control Supplementing Speed Variable Hydraulic Drives - Philipp Zagar; Helmut Kogler; Rudolf Scheidl; Bernd Winkler (Actuators, 2020)
Primary control of linear motion by variable speed electric motors driving a hydraulic cylinder via a constant displacement pump is an established and successful concept with a frequent use in industry. One problem arises when low or zero motion speed has to be realized under high pump pressure conditions. Such load scenarios occur frequently in certain pressing processes, e.g., for sintering or veneering. Most pumps have a lower speed limit, below which critical tribological conditions occur which impair lifespan and efficiency. In addition, pump speed control and pump fluctuation suffer from the mixed lubrication conditions in such an operation range. For a circumvention of such low speed pump operation, a digital valve control concept is presented and studied in this paper. Valve control is used in load holding phases with low speed. Pressure is provided by an accumulator which is charged by the pump in short charging cycles at reasonable pump speeds. It is shown that the mean control error during load holding phase lies within the desired band and the fluctuations of the control force are lower than those of the pump control. In addition, the unfavorable pump operation conditions can be avoided via digital control.